National Microbiological Laboratory Reporting Service - Bulletin 18. 26 August to 8 September 1977 - whole issue - No author listed (Communicable Diseases Intelligence, 1977)
Whole-issue pdf, comprising: Article Hand, foot and mouth disease. [outbreak in Perth, W.A.] Salmonella chester. [outbreak in Perth, W.A.] U.S. outbreak of salmonella newport transmitted by pre-cooked beef. S. Typhimurium infection. [Melbourne, Vic.] Parvovirus gastroenteritis. [Sydney, N.S.W.] Penicillin resistant gonorrhea. [Australia-wide notifications.] Correction "The returns for notifiable diseases for Tasmania in the week ending 19 August 1977, published in Bulletin 17, should be amended as follows..." [change in notifications follow] Article Influenza. [recent notifications Melbourne, Vic.] Rotavirus. [Melbourne, Vic.] Influenza-like illness amongst Australian troops in Canada. [see report in next Issue] National Microbiological Laboratory Reporting Service - Period 18 26 August to 8 September 1977 Notifiable Diseases in the States and Territories of Australia List A - Communicable diseases notified by medical practitioners, hospitals or diagnostic laboratories. Week ended 19.08.1977 List B - Communicable diseases and agents notified after hospital and laboratory diagnosis. Week ended 19.08.1977 List A - Communicable diseases notified by medical practitioners, hospitals or diagnostic laboratories. Week ended 25.08.1977 List B - Communicable diseases and agents notified after hospital and laboratory diagnosis. Week ended 25.08.1977 List A - Communicable diseases notified by medical practitioners, hospitals or diagnostic laboratories. Week ended 01.09.1977 List B - Communicable diseases and agents notified after hospital and laboratory diagnosis. Week ended 01.09.1977